Carboxymethylchitin Nanocarrier (CMCNC): A Novel Therapeutic Formulation for Drug Release. Issue 1 (2nd January 2019) - Jain, Tanvi; Kumar, Sushil; Dutta, P. K.
ABSTRACT: In the present work, chitin based derivatives carboxymethylchitin, CMC were synthesised for nanocarriers (NCs). Cu and Fu loaded NCs had also been prepared and characterized by various physiochemical & biological techniques. Here, drug release profiles and drug kinetics were also studied. In vitro cytotoxicity test (Cell Viability-A549 cells) result found most effected. CMCNC also fitted best in Higuchi model which proved that this prepared nanocarriers followed the mechanism of diffusion rather than dissolution and degradation. The overall analysis leads to the conclusion that CMCNC found to be a suitable nanocarrier for targeted drug delivery. Graphical Abstract: